2021
DOI: 10.1080/0886022x.2021.1923527
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological analysis of renal biopsies of elderly patients in Northeast China: a single-center study

Abstract: Purpose: To identify the clinical characteristics, histopathological features, and prognosis of kidney disease in a large cohort of elderly patients from Northeast China. Methods: We retrospectively analyzed the renal disease spectrum in 7,122 patients who underwent renal biopsies at the Second Hospital of Jilin University from 2006 to 2020. Patients were grouped according to age: below 60 years (non-elderly group, n ¼ 5923) and at least 60 years (elderly group, n ¼ 1199). The clinical and pathological charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
2
8
0
1
Order By: Relevance
“…The difference between both studies can be explained by the small number of patients included in our cohort compared with the previous study and the difference in ethnic populations between the two studies. DN and hypertensive nephrosclerosis were predominate in the older age group and this was consistence with previous studies (19,20) Our study has some limitations: First, it was of a small sample size which could have a drawback effect on the conclusion of the study. Second, because it was a single center study, the findings might not accurately reflect the prevalence of glomerular diseases at other centers.…”
Section: Outcomes Of Kidney Diseases Diagnosed By Kidney Biopsysupporting
confidence: 86%
See 1 more Smart Citation
“…The difference between both studies can be explained by the small number of patients included in our cohort compared with the previous study and the difference in ethnic populations between the two studies. DN and hypertensive nephrosclerosis were predominate in the older age group and this was consistence with previous studies (19,20) Our study has some limitations: First, it was of a small sample size which could have a drawback effect on the conclusion of the study. Second, because it was a single center study, the findings might not accurately reflect the prevalence of glomerular diseases at other centers.…”
Section: Outcomes Of Kidney Diseases Diagnosed By Kidney Biopsysupporting
confidence: 86%
“…In this study, we have found that the main indication for kidney biopsy was a nephrotic syndrome with abnormal renal function which was present in 30% of patients followed by patients with sub-nephrotic range proteinuria with abnormal renal function in 23% of cases while patients with nephrotic syndrome with normal kidney function were found in 23% of cases. In a previous report (19), the nephrotic syndrome was the most prevalent manifestation in patients who had a biopsy, followed by glomerulonephritis, CKD, and AKI. In our cohort, the most common pathological findings were FSGS in 25% followed by lupus nephritis in 19.6%.…”
Section: Outcomes Of Kidney Diseases Diagnosed By Kidney Biopsymentioning
confidence: 79%
“…Six publications provided evidence on IgAN incidence [ 30 , 61 , 63 , 74 , 77 , 78 ] in Australia ( n = 2), Japan ( n = 2), mainland China ( n = 1), and Taiwan ( n = 1). Most were cross-sectional observational studies ( n = 4), and sample sizes ranged from 156 [ 74 ] to 270,902 [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…по данным ряда исследований, она встречается приблизительной в 4,5% случаев всех биопсий и занимает 7-е место по частоте обнаружения [2]. при этом в возрасте старше 60 лет амилоидная нефропатия обнаруживает- ся в 3,5% случаев, тогда как в возрасте младше 60 лет -только в 0,5% случаев [3]. ещё реже встречается амилоидное поражение почек при амилоидозе других типов (нааа и неAL).…”
Section: вступлениеunclassified